Boro em trevo: eficiência de extratores e efeito sobre atributos químicos do solo, em área com e sem corte da parte áerea submetida a níveis de b - Batista, Cíntia Boeira (2011)
Recently studies have been directed to the importance of micronutrients in plant mineral nutrition. However, there is great difficulty in quantifying micronutrients by chemical analysis of soil due to low reliability of the methods. Extractors used by many laboratories do not have a satisfactory correlation with the amounts found in the analysis of leaf. This study, besides evaluating extractors for soil B, also sought to evaluate the effect of handling the cutting and removal of the aerial part of white clover (Trifolium repens L.) on soil chemical properties. This work aims to: 1ª - to study the efficiency of extraction solutions consisting of aluminum sulfate, sorbitol and Mehlich1 the quantitative assessment of boron in soil and efficiency of extractors when correlated with the results of boron leaf contained in the culture of white clover 2ª - evaluate the influence of the management of cutting and removing the aerial part of white clover on soil chemical properties. In the field the white clover was conducted at the Experimental Station of the Agronomic Institute of Paraná - IAPAR, located in the city of Pato Branco - PR. The experimental area is located in the physiographic region called the Third Paranaense Plateau. The soil is classified as Oxisol clayey wavy relief (EMBRAPA, 2008). The experimental design was randomized blocks with four replications, and plots consist of four collections, the sub plots were the treatments with increasing doses of boron (0, 0.5, 1, 2 and 4 kg ha-1) in the form of ulexite (10% of B). The sub - sub plots were the different soil depths evaluated (0-5, 5-10, 10-20 cm). The soil and plant samples were collected every two months that the plant was being sent to the Laboratory in Londrina IAPAR to determine levels of boron leaf. While the soil samples were analyzed at the Laboratory of Soil UTFPR - Campus White Duck. To evaluate the second experiment was used a randomized block design with four replications subdivided. The samples were treated as two parts, sub-plots were cut and management without cutting the shoots of white clover, sub plots were treated as five doses of B (0, 0.5, 1.0 , 2.0 and 4.0 kg ha-1, using 10% solution Ulexite B) and sub - sub - plots were set up by soil sampling depths (0-5, 5-10 and 10-20 cm). The methodologies used for routine chemical analysis of soil following IAPAR (1992), as well as the analysis of extraction and quantification of B in soil and plant. With the first evaluation finds that the Al 2 (SO4) 3 0.005 M was the extractor that presented higher correlation values between the values of the nutrient in the plant with the same values in the soil of 0.92. It was found that the Ulexite has a slow release of nutrients in the soil B with the highest levels of recovery of B in the soil by different extractants were observed, usually after six months of application. In the second evaluation verifies that the constant removal of the aerial parts of forage causes soil acidification, an increase of toxic elements such as Al and extraction of bases, so production systems of silage and hay must constantly replenish the soil bases through liming.